Stories of detection and mystery (Longman, 1965)
Who has murdered the young Englishman on his return from America? Why have a young couple disappeared from their home? And is there something ghostly about the whimpering sounds heard in a New York storehouse? As the people in these stories try to answer these questions, they realize that the answers may lie where they least expect them.